Noncontrast assessment of blood–brain barrier permeability to water: Shorter acquisition, test–retest reproducibility, and comparison with contrast‐based method. Issue 1 (8th February 2021) - Lin, Zixuan; Jiang, Dengrong; Liu, Dapeng; Li, Yang; Uh, Jinsoo; Hou, Xirui; Pillai, Jay J.; Qin, Qin; Ge, Yulin; Lu, Hanzhang
Abstract : Purpose: Assessment of the blood–brain barrier (BBB) permeability without the need for contrast agent is desirable, and the ability to measure the permeability to small molecules such as water may further increase the sensitivity in detecting diseases. This study proposed a time‐efficient, noncontrast method to measure BBB permeability to water, evaluated its test–retest reproducibility, and compared it with a contrast agent–based method. Methods: A single‐delay water extraction with phase‐contrast arterial spin tagging (WEPCAST) method was devised in which spatial profile of the signal along the superior sagittal sinus was used to estimate bolus arrival time, and the WEPCAST signal at the corresponding location was used to compute water extraction fraction, which was combined with global cerebral blood flow to estimate BBB permeability surface area product to water. The reliability of WEPCAST sequence was examined in terms of intrasession, intersession, and inter‐vendor (Philips [Ingenia, Best, the Netherlands] and Siemens [Prisma, Erlangen, Germany]) reproducibility. Finally, we compared this new technique to a contrast agent–based method. Results: Single‐delay WEPCAST reduced the scan duration from approximately 20 min to 5 min. Extract fraction values estimated from single‐delay WEPCAST showed good consistency with the multi‐delay method (R = 0.82, P = .004). Group‐averaged permeability surface area product values were found to be 137.5 ± 9.3 mL/100 g/min. Intrasession, intersession, and inter‐vendor coefficient of variation of the permeability surface area product values were 6.6 ± 4.5%, 6.9 ± 3.7%, and 8.9 ± 3.0%, respectively. Finally, permeability surface area product obtained from WEPCAST MRI showed a significant correlation with that from the contrast‐based method (R = .73, P = .02). Conclusion: Single‐delay WEPCAST MRI can measure BBB permeability to water within 5 min with an intrasession, intersession, and inter‐vendor test–retest reproducibility of 6% to 9%. This method may provide a useful marker of BBB breakdown in clinical studies.